Nitrous oxide and methane in a changing Arctic Ocean - Rees, Andrew P.; Bange, Hermann W.; Arevalo-Martinez, Damian L.; Artioli, Yuri; Ashby, Dawn M.; Brown, Ian; Campen, Hanna I.; Clark, Darren R.; Kitidis, Vassilis; Lessin, Gennadi; Tarran, Glen A.; Turley, Carol (Ambio, 2022)
Human activities are changing the Arctic environment at an unprecedented rate resulting in rapid warming, freshening, sea ice retreat and ocean acidification of the Arctic Ocean. Trace gases such as nitrous oxide (N2O) and methane (CH4) play important roles in both the atmospheric reactivity and radiative budget of the Arctic and thus have a high potential to influence the region's climate. However, little is known about how these rapid physical and chemical changes will impact the emissions of major climate-relevant trace gases from the Arctic Ocean. The combined consequences of these stressors present a complex combination of environmental changes which might impact on trace gas production and their subsequent release to the Arctic atmosphere. Here we present our current understanding of nitrous oxide and methane cycling in the Arctic Ocean and its relevance for regional and global atmosphere and climate and offer our thoughts on how this might change over coming decades.